The Autobiographical Story as an Educational Method: Theory, Authors, and Cases - Dittus, Rubén (Advances in Social Sciences Research Journal, 2023)
This paper synthesizes the recent theoretical debate around the relationship that autobiographical writing has with the educational process and its improvements. The evidence indicates that learning based on autobiographical stories for meaningful and active teaching also generates a psychosocial effect from an early identification of difficulties and alerts on the affective level. In a preliminary version, this work was prepared and written by the author as a theoretical framework for the project "Portfolio of autobiographical narratives for the development of writing and socio-affective skills in students entering the Central University of Chile" (2018-2019), in which the researchers Marcela Amaya García, Alejandra Riveros, Rubén Dittus, Georg Unger and Felipe Trujillo participated. The compilation of the bibliographical sources that are presented here are the result of the diligent work of Seidy Zevallos, research assistant. The theoretical reflection was later complemented and collated in the workshops that the team organized with students from the Faculty of Communications based on instruments prepared by Georg Unger, an academic around Psychology, and whose results were published in other documents.